Evaluating pharmacy students’ perceptions of depression and psychotropic medicines in the Hashemite Kingdom of Jordan - Al jomaa, Esraa; Abdel-Qader, Derar; Hamadi, Salim (Jordan Journal of Pharmaceutical Sciences, 2021)
Background: Although enhancing of pharmacy students’ knowledge and perceptions of mental illness is important for future career development, the pharmacy curricula in Jordan are largely deficient in mental health courses and no study has examined the attitudes of pharmacy students towards mental illness and their knowledge on psychotropic medicines in Jordan. Objective: To evaluate pharmacy students’ knowledge on depression and psychotropic medicines and to assess their attitudes towards providing pharmaceutical care (PPC) to patients with depression. Method: A cross-sectional emailed survey was conducted on a purposive sample of 200 pharmacy students who were in 4th and 5th level in one Jordanian university. The questionnaire included four sections; demographics, knowledge on depression, attitude towards PPC to patients with depression, and knowledge on psychotropic medicines. Chi-square testing was used to determine significant relationships between demographics and other statements. Results: A total of 134 responses were received (response rate 67%). Most of students believed that patients with depression will not take antidepressants forever (n=104, 77.6%). Less than half (n=60, 44.8%) of students thought that antidepressants do not cause addiction. Eighty-seven students (64.9%) were able to monitor efficacy and adverse effects of antidepressants. Only about a third (n=52, 38.8%) of students knew venlafaxine, and 47.0% of students (n=63) didn’t know vortioxetine. Having training courses on psychiatry were significantly associated with knowledge of pharmacy students in psychiatry (p<0.05). Conclusion: Despite students expressed positive attitude towards PPC to patients with depression, pharmacy students should improve their knowledge on psychiatric pharmacotherapy. Policy makers should include courses on psychiatric disorders and pharmacotherapy in university curricula.